Penghijauan Dalam Rangka Mengurangi Dampak Pemasanan Global Di Bidang Pertanian Di Jorong Pakan Baru Nagari Taram - husnarti husnarti; Rahmawati Rahmawati; Revi Ernanda; Yustitia Akbar; Desriana Desriana; Yunita Sabri (Pengelola Jurnal Politeknik Negeri Ketapang, 2023)
Global warming is a challenge faced by the agricultural sector because global warming has resulted in a decrease in production and productivity of food crops caused by natural disasters, one of which is flooding. Nagari Taram, which is a producer of food crops, especially rice, in Harau District is an area prone to flooding. So that when this area is hit by floods it will cause a decrease in rice production. Therefore, it is necessary to do afforestation as a long-term flood management strategy. The reforestation was carried out in the Kapalo Banda river basin. The plants planted are ketapang trees because ketapang trees are trees that provide many benefits such as being a shade, neutralizing the pH of water, the seeds are consumed, as building materials and most importantly the extract can be used by farmers for herbicides. It is hoped that this greening will provide knowledge, examples and motivation for the local community so that later this greening will continue to the lower reaches of the Kapalo Banda river.